Damage evolution characterization of glass fabric composites at cryogenic temperatures via in-situ tensile X-ray computed tomography tests. (November 2022) - Li, Yuanchen; Wei, Yong; Meng, Jinxin; Zhang, Ling; Wang, Panding; Zheng, Huayong; Lei, Hongshuai
Abstract: The woven fabric composites (WFCs) are promising materials for cryogenic applications. The internal microstructure of composites influences the cryogenic mechanical properties obviously. However, few works focused on the microstructure and damage evolution process of WFCs at cryogenic temperature. The mechanism of cryogenic effect on WFCs is still unclear due to the lack of in-situ characterization of damage evolution at different cryogenic temperatures. Herein, novel cryogenic in-situ tensile tests with micro X-ray-computed tomography ( μ CT) were designed to study the microstructure and morphology evolution of glass/epoxy WFCs. The damage evolution processes of glass/epoxy WFCs under tension at 293 K, 173 K, and 93 K were elucidated via in-situ CT scanning and 3D reconstruction. The results indicate that the initiation of multiple transverse cracks within the weft yarns and delamination damage are the primary microscale characteristics of glass/epoxy WFCs at low temperatures. The initiation of cracks and delamination damage promote the release of mechanical energy and decrease the effect of initial manufacturing defects, which are the main strengthening mechanisms of the glass/epoxy WFCs under tension at cryogenic temperature. Graphical abstract: Image 1 Highlights: In-situ computed tomography tensile tests were performed at cryogenic temperature. Damage evolution of composites was quantified at cryogenic temperature. Interlayer delamination was demonstrated as the primary cryogenic failure mechanism.